2012
DOI: 10.1364/oe.20.005530
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature polariton lasing vs photon lasing in a ZnO-based hybrid microcavity

Abstract: We report on the room temperature polariton lasing and photon lasing in a ZnO-based hybrid microcavity under optical pumping. A series of experimental studies of the polariton lasing (exciton-photon detunings of δ = -119 meV) in the strong-coupling regime are discussed and compared to a photon lasing (δ = -45 meV) in the weak-coupling regime obtained in the same structure. The measured threshold power density (31.8 kW/cm2) of polariton lasing is one order of magnitude lower than that of the photon lasing (318.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 37 publications
0
64
0
Order By: Relevance
“…15,16 Although polariton lasing has been mainly observed at low temperature due to the small binding energy typical of Wannier-Mott excitons, 13 recent developments have led to room temperature demonstrations in III-nitrides and ZnO. 17,18,19,20 Frenkel excitons possess binding energies of ~ 1 eV and are thus highly stable at room temperature. 21 Organic polariton lasing was first demonstrated in microcavities containing anthracene single-crystals.…”
mentioning
confidence: 99%
“…15,16 Although polariton lasing has been mainly observed at low temperature due to the small binding energy typical of Wannier-Mott excitons, 13 recent developments have led to room temperature demonstrations in III-nitrides and ZnO. 17,18,19,20 Frenkel excitons possess binding energies of ~ 1 eV and are thus highly stable at room temperature. 21 Organic polariton lasing was first demonstrated in microcavities containing anthracene single-crystals.…”
mentioning
confidence: 99%
“…Later, Franke et al 39 pushed the operation temperature of the ZnO polariton lasing up to 250 K by depositing a polycrystalline ZnO inside two dielectric distributed Bragg reflectors (DBRs). One month later, Lu et al 40 successfully demonstrated the first RT polariton lasing in ZnObased hybrid microcavities with an ultra-low threshold. Das et al 41 followed with a method similar to that in their previous report on GaN nanowire MCs and observed polariton lasing in a fully dielectric DBRbased MC.…”
Section: Progress Historymentioning
confidence: 99%
“…Coherent matter-field interaction can be achieved in this case at room temperatures by using wide-band (ZnO) semiconductor microstructures, cf. [24].…”
Section: Introductionmentioning
confidence: 99%